The Main Cause of Variation of the Unemployment Percentage Between Industries–A Correction - Champernowne, D. G. (Review of Economic Studies, 1939)
Journal Article The Main Cause of Variation of the Unemployment Percentage Between Industries—A Correction Get access D. G. Champernowne D. G. Champernowne Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 2, February 1939, Pages 125–126, https://doi.org/10.2307/2967395 Published: 01 February 1939